All the Dead Shall Weep: Gunnie Rose #5 - Harris, Charlaine (New York : Saga Press, 2023)
"Following the murderous events of Serpent of Heaven, Lizbeth Rose is awaiting the arrival of her sister Felicia and her husband's younger brother Eli in Texoma. Both needed to leave the seat of the Holy Russian Empire in San Diego after Felicia's burgeoning wizardly power in death magic became the reason for kidnapping and assassination attempts from her mother's family of high-powered wizards in Mexico. Yet bad news has traveled ahead of them, as Eli is called back to San Diego, taking Peter along with him, splitting them apart in more ways than one as their enemies' plans for revenge come to fruition"--.
New Book Winter 2023.
Keywords: Witches -- Fiction; Families -- Fiction; Sisters -- Fiction; Brothers -- Fiction; Wizards -- Fiction; Magic -- Fiction; Revenge -- Fiction; San Diego (Calif.) -- Fiction; Alternative histories (Fiction); Witch fiction; Thriller fiction; Paranormal fiction; Mystery fiction; Fantasy fiction